Enhancing History Education: Evaluating the Impact of the Reciprocal Teaching Method on Students' Reading Comprehension in History Subjects - Thiago, Acher Philipus; Malikha, Lashira (Jurnal Ilmu Pendidikan dan Humaniora, 2024)
This research delves into the efficacy of the Reciprocal Teaching Method in enhancing students' reading comprehension within the realm of history education. The study adopts a quasi-experimental design, comparing the impact of the method against traditional instructional approaches within a specific group of history classrooms. A combination of quantitative and qualitative data sources, including pre- and post-assessments, classroom observations, and questionnaires, illuminates the method's influence on students' comprehension and engagement. The findings showcase a significant improvement in reading comprehension among students who underwent instruction using the Reciprocal Teaching Method, compared to a control group following traditional instructional practices. The method's structured and collaborative nature fosters active engagement with historical texts, propelling critical thinking skills and a deeper understanding of historical narratives. Moreover, the research emphasizes the adaptability of the method to cater to varied learning profiles, thereby advocating for inclusive pedagogical approaches within history education. The implications of the study extend to the reconfiguration of history education, calling for a shift toward interactive and engaging pedagogical strategies that nurture comprehensive understanding and critical engagement among students. This research marks a significant stride toward empowering students within history classrooms, pointing towards a transformative era in history education and paving the way for informed, engaged citizens well-versed in the complexities of the past.